2014
DOI: 10.1039/c3cp55306j
|View full text |Cite
|
Sign up to set email alerts
|

The strong catalytic effect of Pb(ii) on the oxygen reduction reaction on 5 nm gold nanoparticles

Abstract: Citrate-capped gold nanoparticles (AuNPs) of 5 nm in diameter are synthesized via wet chemistry and deposited on a glassy carbon electrode through electrophoresis. The kinetics of the oxygen reduction reaction (ORR) on the modified electrode is determined quantitatively in oxygen-saturated 0.5 M sulphuric acid solution by modelling the cathode as an array of interactive nanoelectrodes. Quantitative analysis of the cyclic voltammetry shows that no apparent ORR electrocatalysis takes place, the kinetics on AuNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The electron-transfer rate constant of the rate-determining step and the transfer coefficient measured from AuNPs of 5~40 nm radii are almost identical with the results on the Au macroelectrode, showing there is no significant nanoeffect on the electrocatalytic kinetics for ORR on Au. [68][69] However, a negative effect was found for 2 nm AuNPs,…”
Section: Oxygen Reduction Reactionmentioning
confidence: 95%
See 1 more Smart Citation
“…The electron-transfer rate constant of the rate-determining step and the transfer coefficient measured from AuNPs of 5~40 nm radii are almost identical with the results on the Au macroelectrode, showing there is no significant nanoeffect on the electrocatalytic kinetics for ORR on Au. [68][69] However, a negative effect was found for 2 nm AuNPs,…”
Section: Oxygen Reduction Reactionmentioning
confidence: 95%
“…Nanoeffects on the ORR kinetics for a series of gold nanoparticles (AuNP) of 2~40 nm radii were investigated by Compton et al via comparing the kinetic parameters measured from AuNP modified electrodes and a gold macroelectrode. 62,[68][69] The mechanism of ORR was inferred to be the twoelectron-two-proton transfer mechanism and the product to be H2O2: 68…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…− that follow the transfer of the first electron [31,32]. In both media, electrochemical techniques such as cyclic voltammetry [33,34], impedance spectroscopy [35], rotating disk [36,37], and ring disk electrode [24,38] and SECM experiments [27] have allowed kinetic features to be reached. Surprisingly, very few works dealing with ORR on AuNPs in neutral media have been reported in the literature [39][40][41] although it would be of great interest for applications such as environmental survey [42] or clinical analysis [43].…”
Section: Introductionmentioning
confidence: 99%
“…However, a strong enhancement of electrocatalytic activity was observed in the presence of small amounts of underpotentially deposited lead. [28] Sarapuu et al studied the electroreduction of O 2 on thin Au films prepared by vacuum evaporation and found that the specific activity (SA) does not depend on film thickness in H 2 SO 4 solution, but in KOH solution the SA decreases with film thickness. [29,30] Zeis et al have demonstrated the high electrocatalytic activity of nanoporous Au for the reduction of O 2 and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%